Comparison of the DOAC Dipstick Test on Urine Samples With Chromogenic Substrate Methods on Plasma Samples in Outpatients Treated With Direct Oral Anticoagulants - Loula Papageorgiou MD, MS; Svetlana Hetjens PhD; Jawed Fareed PhD; Sanny Auge RN; Laetitia Tredler RN; Job Harenberg MD, PhD; Christel Weiss PhD; Ismail Elalamy MD, PhD; Grigorios T. Gerotziafas MD, PhD (Clinical and Applied Thrombosis/Hemostasis, 2023)
Identifying adherence to direct oral anticoagulants (DOACs) plays a major role in treatment efficacy and safety. The DOAC Dipstick can detect DOACs in urine samples of acutely diseased patients at plasma thresholds of about 30 ng/mL. A prospective observational consecutive cohort study was performed on outpatients taking DOACs. The presence of direct oral factor Xa inhibitors (DXIs) in patient urine samples were independently evaluated by visual interpretation of the DOAC Dipstick pad colors. DOAC plasma concentration was assessed using STA®-Liquid Anti-Xa and STA®-Liquid Anti-IIa chromogenic substrate assays. Positive DOAC Dipstick results were compared with a threshold plasma of DOAC concentration ≥30 ng/mL. Of 120 patients (age 55.4  +  16.1 years, female n  =  63), 77 were on rivaroxaban and 43 on apixaban. Plasma concentrations were 129  ±  118 ng/mL for rivaroxaban, and 163  ±  130 ng/mL for apixaban, DOAC Dipstick test has a sensitivity of 97.2% and a positive predictive value of 89.5% at 30 ng/mL. No differences occurred between DXIs. Specificity and negative predictive value could not be determined due to the low number of true negative values. There were no differences in the interpretation of rivaroxaban and apixaban pad colors between observers (Kappa 1.0). Results show that DOAC Dipstick may be a useful tool for identifying DXIs in urine samples in an outpatient setting at a plasma threshold ≥ 30 ng/mL. Further studies should include patients treated with dabigatran, vitamin K antagonists, or other anticoagulants.